The significance of radiology in the context of the Unified Health System (SUS): A literature review (Research, Society and Development, 2023)
Introduction: The integration of radiological services in the healthcare domain is crucial, providing precise diagnostics and guidance for procederes, significantly contributing to the quality of patient care. However, in the Brazilian Unified Health System (SUS), access to these services is challenging due to the high costs associated with large-scale implementation, including investments in expensive equipment and qualified workforce. Despite these initial financial challenges, in the long run, radiology in the SUS demonstrates returns, resulting in more accurate diagnoses, reduced expenses on inappropriate treatments, and prevention of complications. The widespread implementation of radiology not only benefits the healthcare system but also healthcare professionals and, most importantly, SUS-dependent patients. Objective: The objective is to emphasize the importance of radiology in the Brazilian healthcare system, addressing its contribution to diagnostics, treatments, and the overall effectiveness of the system. Methodology:The methodology employed in crafting this literature review was based on research conducted in reputable databases such as the Medical Literature Analysis and Retrieval System Online (MEDLINE) and the Scientific Electronic Library of Medicine (SCIELO). Specific descriptors like "radiology," "SUS," and "performance" were used. Results: The research reveals that access to radiological services in the SUS is restricted due to high costs, highlighting the need for medium-term investments to achieve more accurate diagnoses and reduce expenses associated with inappropriate treatments. Conclusion: Therefore, it is concluded that the integration of radiology into the public healthcare system is a complex process.